2015
DOI: 10.1002/jrs.4782
|View full text |Cite
|
Sign up to set email alerts
|

Low wavenumber Raman scattering of cobalt nanoparticles self‐organized in 3D superlattices far from surface plasmon resonance

Abstract: International audienceWe report the first observation of low wavenumber Raman scattering from cobalt nanoparticles under 514.5nm laser excitation. These 7.4nm diameter particles were self-organized in 3D superlattices, but we assign the Raman signature to vibrations of the individual nanoparticles, according to Lamb’s elastic sphere model. We estimate the relative Raman intensity to be around 500 times lower than it would be for silver nanoparticles, but our results demonstrate that surface plasmon–phonon reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Light in the UV range (<400 nm), coincident with the expected surface plasmon resonance of metallic cobalt nanoparticles, was observed to promote the reaction in a noticeable way. 33 Therefore, it can be deduced that photo-generation of charges (electron-hole pairs) on Co nanoparticles might participate in the CO2 hydrogenation reaction. A recent study on the use of carbon-coated iron nanoparticles in a similar process suggested that hot electrons generated by absorption of UV light were responsible for activating CO2.…”
Section: Effect Of Light On the Catalytic Performancementioning
confidence: 99%
“…Light in the UV range (<400 nm), coincident with the expected surface plasmon resonance of metallic cobalt nanoparticles, was observed to promote the reaction in a noticeable way. 33 Therefore, it can be deduced that photo-generation of charges (electron-hole pairs) on Co nanoparticles might participate in the CO2 hydrogenation reaction. A recent study on the use of carbon-coated iron nanoparticles in a similar process suggested that hot electrons generated by absorption of UV light were responsible for activating CO2.…”
Section: Effect Of Light On the Catalytic Performancementioning
confidence: 99%
“…According to Lamb’s theory, the vibration modes of a free elastic sphere (regular) are described with the azimuthal quantum number . From the selection rules established in refs only vibration modes related to an even value of are Raman active. The lowest wavenumber has a peak at ∼10 cm –1 , and is assigned to the quadrupolar ( = 2) mode, for the second lowest wavenumber mode at 20 cm –1 , it corresponds to the breathing mode ( = 0) .…”
Section: Resultsmentioning
confidence: 99%
“…From the selection rules established in refs only vibration modes related to an even value of are Raman active. The lowest wavenumber has a peak at ∼10 cm –1 , and is assigned to the quadrupolar ( = 2) mode, for the second lowest wavenumber mode at 20 cm –1 , it corresponds to the breathing mode ( = 0) . The narrow size distribution and high stability of NCs against oxidation and coalescence, combined with the high luminosity of the spectrometer at the particular wavenumber interval, made possible the simultaneous observation of both breathing and quadrupolar modes whenever the Plasmon absorption of cobalt metal is expected far away from the laser excitation energy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simon and co‐workers report the first observation of low‐wavenumber Raman scattering of cobalt nanoparticles that were self‐organized into 3D superlattices far from surface plasmon resonance. Their results demonstrate that surface plasmon‐phonon resonance coupling is not required to observe Lamb's modes in metal nanoparticles . Sivadasan and Dhara used polarized Raman and photoluminescence studies of a submicron‐sized hexagonal AlGaN crystallite to study their structural and optical properties.…”
Section: Nanomaterialsmentioning
confidence: 99%